Questioning definitions at university: the case of analysis - Winsløw, Carl (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2019)
Résumé A la base d’un cas particulier, lié à la définition des intégrales curvilignes en analyse vectorielle, nous examinons un dessin modeste visant à réaliser le paradigme du « questionnement du monde » dans l’étude d’un certain type de définition en analyse, et plus généralement les conditions et contraintes rencontrés par ce paradigme dans l’enseignement supérieur des mathématiques. Abstract Based on a case study on task design related to the definition of curve integrals in vector analysis, we examine a modest design for realizing the paradigm of “questioning the world” in the study of a certain type of definition in mathematical analysis, and more generally, the conditions and constraints this paradigm meets in university mathematics education.